State of the Young Child in India - Creches, Mobile (Taylor & Francis, 2020)
This Report is one of the first comprehensive studies on young children in India. It focuses on children under 6 years of age and presents key aspects of their well-being and development. With the highest number of neonatal, infant and under-5 deaths in the world, there is an urgent need to address issues that continue to affect the young child in India. This volume: Introduces two young child indices aggregating selected indicators to separately track child outcomes and child circumstances. Provides an account of the current situation of the young child in terms of physical and cognitive development, access to care, disadvantaged children and major issues that have led to the continued neglect of this age group. Explores the policy and legal framework, fiscal space and the role and obligations of key stakeholders, including the state, private sector, civil society, media and the family. Highlights key recommendations and action points that can help to improve the ecosystem for early childhood care and development. Drawing on specially commissioned technical background papers, supplemented by extensive field experience of Mobile Creches in childcare, this Report will be of interest to practitioners, policymakers and influencers, think tanks and researchers of public policy, development studies, human rights, sociology and social anthropology, as well as general readers.　 The Open Access version of this book, available at http://www.tandfebooks.com/doi/view/10.4324/9781003026488, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license. .